The orophilous relict High Campoese finely-toothed willow communities - Cantoral González, Alberto Luis; Alonso Redondo, Raquel; García González, Marta Eva (Mediterranean Botany, 2020)
This paper examines High Campoese orophilous snowbed dwarf communities of finely-toothed willow Salix breviserrata Flod. The acidophilous, rupicolous and temporihygrophilous character of this species results in a singular floristic composition that is very different from the Salix breviserrata s.l. Picoeuropean communities. Based on the relevés sampled, the authors describe the endemic High Campoese dwarf scrub association Alchemillo alpinae-Salicetum breviserratae, which we ascribe to the Salicetea herbaceae class, where the mildest ecological conditions are represented, accounting for its relict character. These are Sites of Community Importance as stipulated by the European Commission Habitats Directive, which, together with their sensitivity to global climate change stemming from their limited synchorology, underlines their threatened status and the need for conservation policy.